Educators’ Perspectives on Integrating South Sumatran Local Wisdom in English Language Teaching: An Ethnopedagogical Inquiry - Silva, Solange Francielle; Usra, Meirizal; Farida, Farida; Hartono, Hartono; Siahaan, Sardianto Markos (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This qualitative case study explores how South Sumatran English educators integrate local wisdom into language teaching through ethnopedagogical approaches. Conducted at secondary and tertiary institutions across South Sumatra, the research employed semi-structured interviews with five purposively selected educators, complemented by document analysis of syllabi and teaching materials. Participants ranged from early-career to highly experienced teachers, with teaching experience spanning 3 to 31 years across junior high schools, vocational high schools, universities, and language courses. Data were analyzed using reflexive thematic analysis following Braun and Clarke's framework, revealing four primary themes: perceived relevance and benefits, integration strategies, perceived impacts on learning, and implementation challenges. Findings demonstrate that educators strategically incorporate cultural elements, including Pempek cuisine, Songket textiles, Pulau Kemaro legends, and traditional games like Congklak to simultaneously enhance language acquisition and preserve regional heritage. However, implementation faces significant obstacles: inadequate institutional support, limited culturally-relevant resources, insufficient professional development opportunities, and absence of formal assessment frameworks for cultural integration. Despite these challenges, educators exhibit remarkable agency in developing authentic materials and designing culturally-responsive activities that foster students' linguistic competence alongside cultural identity formation. The study contributes theoretically by demonstrating how ethnopedagogy operationalizes culturally-responsive teaching in Indonesian higher education contexts, bridging Ladson-Billings' framework with Ausubelian meaningful learning principles. Practically, findings underscore urgent needs for systematic resource development, targeted faculty training programs, and institutional policy reforms supporting sustainable ethnopedagogical practice.